Pembekalan Teknis Tenaga Kerja Konstruksi Bidang Pekerjaan Gedung dan Bidang Pekerjaan Jalan di Kabupaten Maros, Sulawesi Selatan - Abdurrahman, M. Asad; Latif, Rusdi U.; Arifuddin, Rosmariani; Tjaronge, M. Wihardi; Caronge, M. Akbar; Hamzah, Suharman; Pongmanda, Silman; Suprapti, Ariningsih; Alimuddin, Hardianti (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
The Act Number 2 of 2017 on Construction Services requires construction workers to have competency certification. This provision aims to protect public interests, improve the quality and competitiveness of the national workforce, and ensure that every construction project is carried out by competent professionals. The construction workforce certification process in Indonesia still faces several obstacles, such as limited access to quality training, high certification costs, and minimal socialization and awareness of the importance of certification. Therefore, Civil Engineering Department, Faculty of Engineering, UNHAS has an important role in supporting the implementation of construction workforce certification by developing a competency-based curriculum, providing practical training, and conducting research related to innovation in the construction sector. Technical training of construction workers in the field of building and road work was carried out for 16 hours of training at the Maros Regent's Office. Participants in this activity were 50 construction workers who met the requirements for level 5 (five) certification. The results of technical briefing for workers who will take part in the work competency certification assessment are indicated to be effective in increasing the readiness and ability of participants to face the certification assessment. Through this training, workers gain a deeper understanding in accordance with competency standards in the field of building and road work, so that they become more confident and competent during the assessment process.